"Bridge to the Literature"? Third‐Party Genetic Interpretation Tools and the Views of Tool Developers. Issue 4 (7th February 2018) - Nelson, Sarah C.; Fullerton, Stephanie M.
Abstract: Patients and health care consumers can obtain access to their "raw, " or uninterpreted, genetic data from direct‐to‐consumer genetic testing companies, researchers, or providers and pursue self‐directed analysis via third‐party interpretation tools. Yet relatively little is known about the nature of currently available interpretation tools or the motivations of tool developers. We conducted a structured content analysis of 23 third‐party interpretation tool websites and supporting information, tracking features such as types of information returned, modes of generating and presenting that information, and privacy and security measures. We additionally conducted qualitative interviews with a subset of 10 tool developers. A majority of tools (16 of 23, or 70%) offer some type of health or wellness‐related information, often extracted from publicly available variant annotation databases. Half of those interviewed characterized their activities as "bridging" users to the scientific literature rather than interpretation, for which they gave a variety of scientific, ethical, and regulatory justifications. The scale, heterogeneity, and complexity of information available from third‐party interpretation are unprecedented. While developers aim to enlighten and empower tool users, interpretation‐free "bridging" to rapidly evolving databases may instead impose burdens on genetic counselors and other health care providers asked to provide further contextualization and explanation.